Use of Methadone to Reverse Opioid Escalation in a Patient With Surgical Pain. (2nd January 2018) - Jaffar, Muhammad; Cunningham, Gwin; Chandler, Michael; Webb, Thomas
ABSTRACT: Acute pain is a prevalent issue for patients recovering from surgical procedures. Methadone has been recognized as a unique option for treatment of surgical pain due to its multiple mechanisms of analgesia and its potential to decrease tolerance to other opioids. Studies of methadone use in postoperative settings are sparse in part due to safety concerns, such as complex pharmacokinetics, risk of respiratory depression, and association with arrhythmias. In this case study of a 70-year-old male with postsurgical abdominal pain, methadone utilization over a period of 9 days resulted in patient-reported analgesia and aided in de-escalating overall opioid use. More studies are needed to develop guidance on how methadone can be used to relieve pain following surgical procedures.